Neutrophil to lymphocyte ratio, platelet to lymphocyte ratio, lymphocyte to monocyte ratio and Systemic Inflammatory Index in sexually transmitted diseases - Pintea-Trifu, Martina-Luciana; Balici, Silvia-Ștefana; Vică, Mihaela Laura; Leucuța, Daniel-Corneliu; Coman, Horia George; Nemeș, Bogdan; Matei, Horea-Vladi (Medicine and Pharmacy Reports, 2024)
Introduction. Hematologic biomarkers of inflammation may serve as valuable adjuncts in clinical practice, aiding in several aspects such as differential diagnosis, prognostic assessment for patient stratification and monitoring the efficacy of antimicrobial therapy. The aim of this study was to evaluate the efficacy of Neutrophil to Lymphocyte Ratio (NLR), Platelet to Lymphocyte Ratio (PLR), Lymphocyte to Monocyte Ratio (LMR), and Systemic Inflammatory Index (SII) in predicting bacterial sexually transmitted infections (STI). Methods. This prospective study was conducted in the north-west region of Romania and included patients from several medical special units such as dermatology, obstetrics-gynecology, urology, and general practice. The study group comprised patients with a high suspicion of STI, while the control group consisted of healthy subjects. Quantitative data are presented as medians (interquartile ranges). Results. The median values of SII, NLR, and SIRI were higher in the group of subjects with sexually transmitted diseases compared to the control group [604.06 (432.36 - 880.02) vs. 556.89 (388.63 - 874.19); 2.61 (1.57 - 3.3) vs. 2.29 (1.66 - 3.26); and 0.95 (0.53 - 1.52) vs. 0.89 (0.67 - 1.34)]. Regarding PLR, the median values were lower in the group of subjects with sexually transmitted diseases compared to the control group [138.1 (99.19 - 169.6) vs. 140.65 (117 - 190.32)]. As for LMR, the median values were equal between the two groups [4.64 (3.74 - 6.11) vs. 4.64 (3.75 - 5.45)]. Nevertheless, the differences did not reach the significance level. Conclusion. Our study suggests that inflammatory biomarkers might aid in detecting bacterial STIs, but their significance was not statistically confirmed. Further research on alternative laboratory tests is needed for improved STI diagnosis and management.